Position-specific Physical Performance of Professional Players during Full-Season Matches in a Greek Superleague Elite Team - Mitrotasios, M.; Ispyrlidis, I.; Mantzouranis, N.; Vassiliades, E.; Armatas, V. (Central European Journal of Sport Sciences and Medicine, 2022)
The aim of the present study was to examine how various playing positions and opponent team ranking affect the covered distances and the acceleration and decelerations profile of a team during 2018-19 Greek SuperLeague. StatSport GPS system recorded in match-play real-time both the players` covered distances (m) and the number of acceleration/deceleration runs (n) in zones from 3 m/s2 to 10 m/s2. The descriptive statistics showed that the players` mean covered distances were 10289 m per match. The MANOVA revealed significant differences of the players` covered distances in all intensity zones in relation to their playing positions (F(12, 513.567)=41.862; p=0.000) and the opponent team ranking (F(3,189)=3.687; p=0.013). Furthermore, no significant interactions were observed between the playing positions and the opponent team ranking (F(12, 500.339)=1.149; p=0.318). Moreover, no significant differences were recorded regarding the opponent team ranking with the amount of accelerations (F(1,189)=0.501; p=0.480) and decelerations (F(1,189)=1.342; p=0.248). Summarizing, the current study showed the high-demanding competitive performance of midfielders, full backs and forwards regardless the standing of the opponent teams. Hence, the team`s training must include special stimuli of aerobic and high-intensity workouts according to the players` playing positions in the match.